IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH RIDDLE GAME - Nasution, Puspita Sari; Daulay, Sholihatul Hamidah; Santoso, Didik (TELL - US JOURNAL, 2023)
In this research, Classroom Action Research (PTK) was used to determine whether students' vocabulary mastery was better with the Riddle game. This research involved 49 students in class VIII SMP IT Nurul Ilmi. The aim is to improve students' vocabulary mastery through playing Riddles. This study was carried out in two cycles, with planning, implementation, observation and reflection included. Quantitative and qualitative data were collected. The results of observations and interviews were used to obtain qualitative data. Students' vocabulary scores in pre-test, post-test, and questionnaires are sources of quantitative data. The research results showed that students mastered vocabulary better, as shown by the average pre-test score of 53.3, the average post-test 1 score of 70.9, and the average pot-test cycle 2 score of 83.5. Apart from that, there were 4 students (8.16%) who met the Minimum Completeness Criteria (KKM) in the pre-test. In cycle 1, there were 27 students (55.1%) who met the KKM, and the results obtained were that 42 students (85.7%) met the KKM in the post-test cycle 2. Thus, the success criteria were achieved. The results of the questionnaire then showed that the Riddle game increased the vocabulary learning response. The results of observations and interviews show that students are motivated in the teaching and learning process when using the Riddle game with an average pre-questionnaire score of 47%.09% after the questionnaire becomes 94.8%, this has increased by 47.71%.